2008
DOI: 10.1002/esp.1692
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion regimes in southeast Texas rivers

Abstract: Avulsions -relatively sudden changes in course, or establishment of new anabranches -are an important process in alluvial rivers. Their key role in floodplain construction and alluvial architecture, and the general conditions favouring avulsions, are well known. However, avulsion processes and evolution, and the factors controlling avulsion regimes, are poorly understood. In the southeast Texas coastal plain, where avulsions are common features of the river valleys, avulsions were studied on the lower Brazos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 35 publications
(80 reference statements)
1
61
0
Order By: Relevance
“…Recent reviews of debates about the Quaternary geologic framework and sea level history of the region are provided by Blum et al (2002), Rodriguez et al (2004), andOtvos (2005). More detailed information on the lower Brazos River area is given by Sylvia and Galloway (2006), Phillips (2007aPhillips ( , 2009a and Taha and Anderson (2008).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of debates about the Quaternary geologic framework and sea level history of the region are provided by Blum et al (2002), Rodriguez et al (2004), andOtvos (2005). More detailed information on the lower Brazos River area is given by Sylvia and Galloway (2006), Phillips (2007aPhillips ( , 2009a and Taha and Anderson (2008).…”
Section: Study Areamentioning
confidence: 99%
“…The coastal plain of Texas is no exception. Notwithstanding debates and uncertainties about the pace and timing of sea level changes, and of Quaternary climate variations, several recent efforts have been made to untangle the influence of climate and sea-level on observed features of alluvial valleys in the region (e.g., Morton et al, 1996;Blum and Price, 1998;Otvos, 2005;Blum and Aslan, 2006;Sylvia and Galloway, 2006;Phillips and Slattery, 2008;Taha and Anderson, 2008;Phillips, 2009a).…”
Section: Sea Level Climate and Coastal Plain Riversmentioning
confidence: 99%
“…However, work on a number of river systems shows that while the setup factors are necessary conditions for avulsions to occur, they are not sufficient, and do not allow for prediction of where and when avulsions occur (e.g. Jones and Schumm, 1999;Makaske et al, 2002;Aslan et al, 2005;Taha and Anderson, 2008;Phillips, 2009). …”
Section: Introductionmentioning
confidence: 97%
“…In rivers of southeast Texas, Phillips (2009) found that valley aggradation state was a first-order control of differences in avulsion in regimes, but that antecedent, inherited morphology was an important second-order control, and local, contingent trigger factors a thirdorder control. Thus five rivers with the same general set of environmental controls showed five different avulsion regimes.…”
Section: Introductionmentioning
confidence: 97%
“…Overbank flows and avulsion processes may directly affect the genesis of several soil properties, such as: a) the formation of a textural gradient, where fine sediments of floodplains are overlaid with sediments deposited in the avulsion process (Smith et al, 1989;Farrell, 2001); b) textural contrast in deeper layers formed due to the burial of avulsion sediments (Phillips, 2009); c) alternate horizons with different textures (fluvic characteristic -Embrapa, 2006;FAO, 2006), formed from overbank flows caused by floods (Cazanacli & Smith, 1998), among other combinations of sediment deposition.…”
Section: Introductionmentioning
confidence: 99%